A5 1 Engulfing the Earth - Matkin, Eleanor; Morriss, Luke; Shkullaku, Marin (Physics Special Topics, 2023)
In this paper we calculate the number of cows that, if the Sun was replaced with a black hole of equal mass, would be needed to be sent into the black hole for the black hole to engulf the Earth. We find that 1.007 × 10^35 cows are required to increase the Schwarzschild radius such that the Earth is swallowed by the black hole, which is many orders of magnitude greater than the number of cows on Earth, making this an astronomically impractical method of destroying the Earth.